Response of dissolved organic matter and bacterial community to anthropogenic disturbances in a plateau lake - Meng, Yue; Jiang, Xin; Li, Yue; Qing, Chun; Long, Xingyu; Xia, Pinhua (Frontiers in Microbiology, 2025)
IntroductionDissolved organic matter (DOM) and bacterial communities play essential roles in lake ecosystem biogeochemical cycles. However, the effects of anthropogenic disturbances on their interactions are not fully understood.MethodsThis study used UV-vis techniques, excitation-emission matrix parallel factor analysis, and 16S rRNA sequencing to reveal the differences in the structures of fluorescent DOM (FDOM) and bacterial communities in lake sediments and water under different levels of anthropogenic disturbances. Methods such as Spearman correlation analysis, null model, neutral community model and random forest analysis were explored how FDOM composition and bacterial communities respond to anthropogenic disturbances in the sediments and water of the Caohai Lake.ResultsThe results indicated that sediment FDOM was sensitive to anthropogenic disturbances, with protein-like substances dominating heavily disturbed areas (69%) and humic-like substances dominating less disturbed areas (63%). However, no significant difference in FDOM composition was found in the water. Similarly, α and β diversity indices for bacterial communities showed no marked variation (P > 0.05) between highly and lightly disturbed areas in both water and sediment samples. Nevertheless, co-occurrence network analysis revealed more negatively correlated links and longer average path length with stronger disturbances. This suggests that while the intensity of anthropogenic disturbance has not yet reached a threshold sufficient to alter the structure of the bacterial community, it might have influenced the types and quantities of resources accessible to the community. Consequently, bacteria might have responded to these changes through competitive interactions, enabling them to resist environmental fluctuations. We found that anthropogenic disturbances were positively linked stochastic processes in the bacterial community assembly and influenced groups that degraded terrestrial humic-like substances. Moreover, the sources and fluorescence components of DOM could have shaped bacterial diversity and community assembly.DiscussionOverall, these findings illustrate that anthropogenic disturbance affects FDOM composition and its relationship with bacteria, providing valuable insights for managing shallow lake ecosystems.